The pottery from the Bronze Age settlement at Podsmreka in the Dolenjska region - Murgelj, Ida (Arheološki vestnik, 2022)
Excavations at Podsmreka near Višnja Gora unearthed a Bronze Age settlement and associated five burials of children or juvenile individuals. They brought to light a wealth of finds that include accumulations of red mudstone, yellow siltstone and bauxite cobbles, the collecting and processing of which was an important activity of the settlement’s inhabitants, but also quantities of pottery that is the topic of this contribution discussing, more particularly, its typological and chronological attribution. Together with the pottery from Oloris, it defines the phenomenon that is the Oloris-Podsmreka horizon, which covers the Middle and transition to the Late Bronze Age in the south-eastern Alpine area.